Longitudinal Study of New Diabetes Cases at Seven Years in a Risk-Sample of Peruvian Subjects with Elevated 1-Hour Ogtt - Lizarzaburu-Robles, Juan Carlos; Garro-Mendiola, Alonso; Vento, Flor (The American heart journal, 2022)
Several studies have recommended the evaluation of the first hour during the OGTT(1hr-OGTT) as a criterion for prediabetes, as it is an earlier biomarker of dysglycemia and is associated with a worse cardiometabolic profile. A cut-off points ≥155mg/dl (8.6mmol/L) in the 1hr-OGTT has been suggested to identify subjects at risk of developing T2DM. We evaluate the incidences of T2DM at seven years (7yrs) among subject with 1-hrOGTT ≥ 155 mg/dl. 115 consecutive subjects with past-history of IFG (Impaired fasting glucose), assessed at the previous study of our group“ 1-Hour OGTT and Metabolic Syndrome”, were evaluated at the outpatient-clinic of the Air-Force-Central Hospital in Lima-Perú. New cases of T2DM were registered during 7yrs period. Patients who were not diagnostic of T2DM, were performance a new OGTT at 7yrs of the initial control. The mean age was 56.88 ± 9.74 years, and 79 (68.7%) were females. We found 22 new cases of T2DM (19%), 16 subjects in the group with 1-hrOGTT ≥ 155 mg/dl (n= 53) (P<0.05), and 10 subjects in the group with impaired glucose tolerances (IGT) (n= 39) (P<0.05). In our sample, subjects with past-history of IFG who had 1-hour glucose levels ≥155 mg/dL after performing an OGTT, had significantly more risk to develop T2DM at 7yrs than those with 1-hour<155 mg/dL. These preliminary results may be helpful to use 1-hrOGTT, as a criterion to identify high-risk subjects to develop T2DM and suggest an early intervention in the same way as it is done for patients with IGT.